Antibody response patterns in COVID‐19 patients with different levels of disease severity in Japan. Issue 5 (9th March 2021) - Imai, Kazuo; Kitagawa, Yutaro; Tabata, Sakiko; Kubota, Katsumi; Nagura‐Ikeda, Mayu; Matsuoka, Masaru; Miyoshi, Kazuyasu; Sakai, Jun; Ishibashi, Noriomi; Tarumoto, Norihito; Takeuchi, Shinichi; Ito, Toshimitsu; et al.
Abstract: We analyzed antibody response patterns according to the level of disease severity in patients with novel coronavirus disease 2019 (COVID‐19) in Japan. We analyzed 611 serum specimens from 231 patients with COVID‐19 (mild, 170; severe, 31; critical, 30). Immunoglobulin M (IgM) and IgG antibodies against nucleocapsid protein (N) and spike 1 protein (S1) were detected by enzyme‐linked immunosorbent assays. The peaks of fitting curves for the optical density (OD) values of IgM and IgG antibodies against N appeared simultaneously, while those against S1 were delayed compared with N. The OD values of IgM against N and IgG against both N and S1 were significantly higher in the severe and critical cases than in the mild cases at 11 days after symptom onset. The seroconversion rates of IgG were higher than those of IgM against both N and S1 during the clinical course based on the optimal cut‐off values defined in this study. The seroconversion rates of IgG and IgM against N and S1 were higher in the severe and critical cases than in the mild cases. Our findings show that a stronger antibody response occurred in COVID‐19 patients with greater disease severity and there were low seroconversion rates of antibodies against N and S1 in the mild cases.